2021
DOI: 10.1007/s12288-021-01433-w
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib in Patients with Relapsed or Refractory Diffuse Large B-Cell Lymphoma: A Retrospective Study

Abstract: Limited treatment options are available for relapsed or refractory diffuse large B cell lymphoma (RR DLBCL). Few clinical studies have reported the use of Ibrutinib, a covalent Bruton Tyrosine kinase (BTK) inhibitor, in RR DLBCL. There are relatively few clinical studies about Ibrutinib in RR DLBCL now. We retrospectively investigated the safety and efficacy of Ibrutinib (alone or in combination with other drugs) in patients with RR DLBCL. We reviewed the medical records of 40 RR DLBCL patients who received Ib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 50 A study about the treatment of DLBCL with ibrutinib revealed that a combination with other drugs such as lenalidomide leads to markedly better prognosis. 51 For the treatment of BL, it might be beneficial to combine the inhibition of tonic BCR survival signals, such as PI3K, with SHIP protein inhibition. Because of its ubiquitous expression, inhibition of SHIP2 might cause more side effects than the inhibition of SHIP1, which is mainly found in cells of hematopoietic origin.…”
Section: Discussionmentioning
confidence: 99%
“… 50 A study about the treatment of DLBCL with ibrutinib revealed that a combination with other drugs such as lenalidomide leads to markedly better prognosis. 51 For the treatment of BL, it might be beneficial to combine the inhibition of tonic BCR survival signals, such as PI3K, with SHIP protein inhibition. Because of its ubiquitous expression, inhibition of SHIP2 might cause more side effects than the inhibition of SHIP1, which is mainly found in cells of hematopoietic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal activation of BTK-regulated BCR signaling pathway was reported as an important driver of the pathogenesis of DL-CBL 10) . As an irreversible inhibitor of BTK, ibrutinib plays an anti-cancer role in diverse B-cell malignancies, especially DLBCL 11,12) . In spite of the positive role of ibrutinib in DLBCL treatment, drug resistance hinders its effectiveness 13) .…”
Section: Introductionmentioning
confidence: 99%